Sistem Informasi Perpustakaan Berbasis Web Dengan Penerapan Metode Rocchio Relevance Feedback - Rifqi Haidar Al-Aziz Rifqi; Kiky Rizky Nova Wardani (PPPM Institut Teknologi Pagar Alam, 2025)
The advancement of information and communication technology has driven significant transformation in the management of educational libraries. SMA Negeri 1 Ujan Mas, which holds a collection of 20,208 books and serves 596 students, still relies on manual procedures for borrowing, returning, and searching library items. This manual system results in slow services, potential inaccuracies in record-keeping, and difficulties in locating books within a large collection. To address these issues, a web-based library information system was developed by implementing the Rocchio Relevance Feedback method and the Waterfall software development model. The Rocchio method was applied to improve search accuracy through user feedback, while the Waterfall model ensured a structured and systematic development process. System evaluation was carried out using Black Box Testing and user assessments. The results indicate that all core functions operated according to requirements, achieving a 100% success rate in functional testing. User evaluations further confirmed that the system is feasible and valid for operational use. The implementation of this system has proven to enhance data management efficiency, accelerate library services, and provide more relevant book searches and recommendations for students and teachers at SMA Negeri 1 Ujan Mas